1994
DOI: 10.1128/aac.38.11.2633
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antibacterial activity of himastatin, a new antitumor antibiotic from Streptomyces hygroscopicus, by fatty acid sodium salts

Abstract: Himastatin, a cyclohexadepsipeptide antibiotic, had in vivo antitumor activity against localized P388 leukemia and B16 melanoma but had no distal site antitumor activity. An Himastatin is a dimeric cyclohexadepsipeptide antibiotic isolated from fermentation broths of Streptomyces hygroscopicus (9, 10). The proposed structure of himastatin is shown in Fig. 1. The compound had antimicrobial activity against grampositive bacteria and was cytotoxic to mammalian tumor cell lines in vitro. Himastatin also was acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Separately, the similarity in MIC values and cellular morphology among our series of synthetic himastatin stereoisomers reveals that achiral interactions—for example, with the hydrophobic groups of phospholipids ( 34 , 35 )—are largely responsible for the observed antibiotic activity. In summary, our chemical biology studies using our synthetic probes offer findings that are consistent with the hypothesis that (–)-himastatin’s ( 1 ) antibiotic activity is dependent on interaction with bacterial membranes ( 7 ). It is evident that (–)-himastatin ( 1 ) is a distinct member among known membrane disruptors ( 41 ).…”
supporting
confidence: 84%
“…Separately, the similarity in MIC values and cellular morphology among our series of synthetic himastatin stereoisomers reveals that achiral interactions—for example, with the hydrophobic groups of phospholipids ( 34 , 35 )—are largely responsible for the observed antibiotic activity. In summary, our chemical biology studies using our synthetic probes offer findings that are consistent with the hypothesis that (–)-himastatin’s ( 1 ) antibiotic activity is dependent on interaction with bacterial membranes ( 7 ). It is evident that (–)-himastatin ( 1 ) is a distinct member among known membrane disruptors ( 41 ).…”
supporting
confidence: 84%
“…Separately, the similarity in MIC values and cellular morphology amongst our series of synthetic himastatin stereoisomers reveals that achiral interactions, for example with the hydrophobic groups of phospholipids (34,35), are largely responsible for the observed antibiotic activity. In summary, our chemical biology studies using our synthetic probes offer findings that are consistent with the hypothesis that (-)-himastatin's (1) antibiotic activity is dependent on interaction with bacterial membranes (7). It is evident that (-)-himastatin (1) is a structurally unique member amongst known membrane-disruptors.…”
supporting
confidence: 83%
“…Compound 3 was observed to lack distal site antitumor activity in vivo. The decrease of bioactivities of 3 in vivo was found to be related to certain fatty acid sodium salts, and it was shown that 3 could be trapped in the micelles formed by the fatty acid salts, which indicated that 3 might execute its inhibition effects by interacting with cell membrane . Compound 1 was also proposed to execute its inhibition effects by damaging cell membrane according to the scanning electron microscope data of cells treated with 1 .…”
Section: Discussionmentioning
confidence: 99%